2012
DOI: 10.1371/journal.ppat.1003073
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Choriomeningitis Virus Infection in FVB Mouse Produces Hemorrhagic Disease

Abstract: The viral family Arenaviridae includes a number of viruses that can cause hemorrhagic fever in humans. Arenavirus infection often involves multiple organs and can lead to capillary instability, impaired hemostasis, and death. Preclinical testing for development of antiviral or therapeutics is in part hampered due to a lack of an immunologically well-defined rodent model that exhibits similar acute hemorrhagic illness or sequelae compared to the human disease. We have identified the FVB mouse strain, which succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…This observation is consistent with a previous report, in which IL‐7‐induced IL‐17 did not result in myeloid cell activation, leading to liver or systematic injury . However, it was also reported that IL‐17 plays a pro‐inflammatory role in Ad infection or LCMV infection in Friend leukemia virus B strain (FVB) mice . The reason for the discrepancies may result from the different viral stocks and murine strains.…”
Section: Discussionsupporting
confidence: 91%
“…This observation is consistent with a previous report, in which IL‐7‐induced IL‐17 did not result in myeloid cell activation, leading to liver or systematic injury . However, it was also reported that IL‐17 plays a pro‐inflammatory role in Ad infection or LCMV infection in Friend leukemia virus B strain (FVB) mice . The reason for the discrepancies may result from the different viral stocks and murine strains.…”
Section: Discussionsupporting
confidence: 91%
“…This suggested that T cell-driven systemic inflammation was essential for LASV pathogenesis, irrespective of viral loads. Analogous observation on T cell dependence of disease were subsequently also reported from two other surrogate models of AHF (Oestereich et al, 2016;Schnell et al, 2012), but the molecular mediators and pathways of AHF pathogenesis, which operate downstream of T cell activation, remain undefined.…”
Section: Introductionsupporting
confidence: 60%
“…Taken together, these observations indicated that the HHD model reproduced the differential susceptibility to LCMV-WE and LCMV-ARM as observed in guinea pigs and non-human primates (Lukashevich et al, 2002;Riviere et al, 1985). Three independent models of AHF have demonstrated T cell dependence of disease (Flatz et al, 2010b;Oestereich et al, 2016;Schnell et al, 2012). Hence, we first investigated whether HHD mice, devoid of murine MHC class I, mounted HLA-A2-restricted CD8 T cell responses to LCMV-WE infection.…”
Section: Lcmv-we Infection Of Hhd Mice Enables the Investigation Of Amentioning
confidence: 78%
“…For example, LCMV Cl-13 inoculation into certain strains of immunocompetent mice (C57Bl/6, Balb/CDJ, C3H, or SWR/J) lead to the persistent infection phenotype. In contrast, the same infection in NZB, SJL, or FVB/N mice induces death by 7 days post-challenge (Baccala et al, 2014; Schnell et al, 2012). The two distinct phenotypes are mediated by IFN-I but, in contrast, to the persistent infection, acute death is primarily due to IFN-α and not IFN-β (Baccala et al, 2014).…”
Section: Differing Roles For Ifn-i Speciesmentioning
confidence: 99%